Synthesis of hierarchical nanozeolites beta and ZSM-5 for green diesel production via hydrodeoxygenation - Arumugam, Mahashanon (2018)
The application of the conventional zeolites has been limited due to its large crystal size (micrometer) and also due to the microporosity (size < 2nm). Hence, this study has been conducted to produce enhanced nanozeolites to overcome the above mentioned limitations. Herein, two microporous nanozeolites namely Beta and ZSM-5 were synthesized via hydrothermal method. Moreover, the enhanced hierarchical nanozeolites have been produced via a green solvothermal approach with the following attributes such as narrow particle size distribution and appropriate mesopores. The synthesis was based on reducing the growth of zeolite crystals by surface silanization of zeolitic seeds using organosilane (hexadecyltrimethoxysilane) as a growth inhibitor. The activities of these nanozeolites and hierarchical nanozeolites were evaluated with catalytic hydroprocessing of oleic acid to green diesel by incorporating Ni metals on these supports. Moreover, extensive characterizations and initial rate investigation were conducted to determine the nature of acid sites and their structuralfunctional relationship in selective hydrodeoxygenation (HDO) of octanoic acid. The results showed hydrothermally synthesized nanozeolites were made of globular aggregates with broader particle size distributions (48-1273 nm for zeolite Beta) and (60-135 nm for zeolite ZSM-5). A much smaller and narrower distributions of globular aggregates of hierarchical nanozeolites are formed using solvothermal approach with sizes of 65–120 nm (for Beta using acetone) and 30-100 nm (for ZSM-5 using 1-decanol). These globular aggregates are actually made by quite smaller primary nanounits ranging 4–11 nm size. The hierarchical nanozeolites exhibited secondary porosity, especially larger mesopores found in zeolite Beta (with pore diameter 8.1 nm) due to efficient functionalization of HDTM in polar solvent environment (acetone). Whereas, moderate mesopores observed in zeolite ZSM-5 (with pore diameter 7.8 nm) caused by the alkoxylation of alcohol based solvent (1-decanol). Catalytic hydroprocessing of oleic acid pointed out higher yields of 60% (consisting of straight and isomeric alkanes C18 and C17) obtained over the microporous nanozeolites than hierarchical nanozeolites at 350 ◦C and 50 bar pressure. This is due to high surface activities demonstrated by the larger external surface areas of microporous nanozeolites. In contrast, the recyclability test of catalysts revealed that hierarchical nanozeolites minimized catalyst deactivation as they were capable of retaining their activities, over 40% (for HZSM-5) and 20% (for HBEA) yields even regenerated after four cycles. As for the initial rate study, all the Ni/zeolite catalysts exhibited higher selectivity towards the octane over the heptane, indicating conversion of octanoic acid occurred preferably via HDO than decarbonylation (DCN) route. The selectivity of the HDO pathway was strongly influence by the Bronsted acid sites of the zeolites. The initial rate studies revealed small Ni metal particles and it’s highly dispersibility over support facilitate high initial catalytic activity. The fatty acid substrate can be quantitatively hydrodeoxgenated to alkanes by cascade reaction on bifunctional catalysts based on Ni and an acidic zeolite. The findings of this study discovered more effective and benign way of producing nanozeolites with high external surface area and hierarchical porosity that provide remarkable HDO activity and better catalyst stability as compared to other commercial support catalysts.